2013
DOI: 10.4103/0974-9233.110617
|View full text |Cite
|
Sign up to set email alerts
|

Ocular blood flow velocity in primary open angle glaucoma - A tropical african population study

Abstract: Purpose:To assess blood flow velocity in newly diagnosed indigenous black-skinned Africans with primary open angle glaucoma (POAG).Materials and Methods:Prospective case-control study at Obafemi Awolowo University Teaching Hospital, Ile-Ife, Nigeria on 50 newly diagnosed POAG patients (POAG group) and 50 control patients (control group). Ocular Doppler Color Imaging was performed on subjects in the supine position using 9 MHz linear array transducer of a Fukuda Denshi Ultrasound. The Peak Systolic Velocity (PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
2
6
1
Order By: Relevance
“…Hauch et al (23) also reported no significant difference regarding this parameter. Olufemi Adeyinka et al (26) also found that the EDV of OA and CRA in glaucoma patients was significantly lower than the control group. Moreover, Ozcan et al (24) reported no significant difference between patients with and without ROP regarding EDV.…”
Section: Discussionmentioning
confidence: 92%
“…Hauch et al (23) also reported no significant difference regarding this parameter. Olufemi Adeyinka et al (26) also found that the EDV of OA and CRA in glaucoma patients was significantly lower than the control group. Moreover, Ozcan et al (24) reported no significant difference between patients with and without ROP regarding EDV.…”
Section: Discussionmentioning
confidence: 92%
“…studied the correlation between arterial resistance and PI in glaucoma patients. [ 15 ] Forty-nine cases of POAG, 62 cases of Normal Tension Glaucoma (NTG), and 48 healthy controls were taken. The RI in OA was found to be 0.81 in normal cases, 0.79 in NTG, and 0.79 in POAG.…”
Section: Discussionmentioning
confidence: 99%
“…in the Tropical African Population in 2013 on 50 cases of newly diagnosed cases of POAG and 50 healthy adults revealed an increase in RI of patients with POAG (0.71 ± 0.05) as compared to normal adults (0.63 ± 0.03) in the OA. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…These differences were found despite statistically similar IOP (Siesky et al 2013). Similarly, a newly published prospective study by Adeyinka et al measured retrobulbar blood flow velocities in African patients with OAG in Nigeria and found reduced peak systolic and end diastolic velocities and increased resistivity in the ophthalmic and central retinal arteries of OAG patients compared to controls (Adeyinka et al 2013). Previous studies have demonstrated a reduction in blood flow velocities in the retrobulbar vessels of glaucoma patients in general (Sergott et al 1994; Nicolela et al 1996; Chiou et al 1999; Akarsu and Bilgili 2004; Abegão Pinto L et al 2012), and lower retrobulbar blood flow within in OAG patients of AD may be a mechanism which contributes to their OAG disease disparity.…”
Section: Ocular (Localized) Vascular Deficiencymentioning
confidence: 98%